(untitled) (LACCEI, 2024)
The covid-19 pandemic had negative economic consequences throughout the world, mainly affecting those who were in a vulnerable situation. In Peru, the incidence of monetary poverty at the household level had a considerable increase at the regional and national levels, reaching the lowest indicators observed during the last five years. In this sense, the objective of the document is to identify the effects of the covid-19 pandemic on the determinants of the incidence of monetary poverty in households headed by women in rural Peru for the year 2021, for this we compare the marginal effects obtained with the results of the year 2019. This contrast is made after obtaining the results through the methodology associated with the probability models, Logit and Probit in Stata, with categorical dependent variable, by maximum likelihood, based on the microdata of the survey of households, corresponding to the years analyzed. Within this analysis we consider characteristics of the heads of household, their environment and housing, which provide us with arguments to discuss the position in the short, medium and long term of public policies based on vulnerable populations.